Experiences of plantation and large-scale farming in 20th century Africa - Peter Gibbon (Danish Institute for International Studies (DIIS), 2011)
The paper's background is a revival of the historically dominant narrative on the large-scale and plantation farming (LSF and PF) in Africa, in reaction to the contemporary phenomenon of 'land grabbing'. The historical antecedents of this narrative are examined and its central contentions - that features including low productivity and limited employment generation normally, if not intrinsically characterize LSF and PF - are problematized. This is undertaken on the basis of comprehensive reviews of the historical and contemporary literatures on African LSF and PF farming and labour control systems.
Keywords: 300; Landwirtschaft; Betriebsgröße; Agrarproduktion; Produktivität; Afrika